A formação e contratação de professores índios e indigenistas no município de Guaíra/PR - JANGARELLI, Silvana Cafa (2018)
This dissertation is linked to the Postgraduate Program in Education of the Oeste Paulista University (known as Unoeste) and to the research line: Public Policies in Education, Formative Processes, and Diversity. The Federal Constitution of 1988 moved forward in the educational policy aimed at indigenous peoples, considering, especially, the proposal of specific and differentiated indigenous school education, bilingualism, and interculturality. These advances constitute the legal guarantee to enable school education and, accomplish the right to education of the indigenous children. The research had as objective the goal of identifying the existence of a hiring and training process of indigenous and indigenist teachers from both state and municipal public-school systems of the Guaíra municipality, state of Paraná, Brazil. To this end, the legal advances made since the Constitution of 1988 were considered, evidencing the demand and all the struggle of the indigenous movement in relation to education. A bibliographical and documentary research was carried out, through survey and analysis of the main legal documents, theses and dissertations repository, as well as specialized literature on this topic. Were considered the documents that address the obligation of federated entities, at both state and municipal levels, to promote training processes in the indigenous language, as well as to hire indigenous teachers. Data regarding the hiring and training of indigenous teachers were collected through the analysis of existing public notices, a survey of documents that evidence the Curriculum and Guidelines of Indigenous Education in the western region of the Paraná state and in the municipality mentioned above. It was found that there are no specific processes of training or hiring for indigenous teachers in the municipality of Guaíra, as well as there are no initiatives at the municipal level for the continuing education of indigenous teachers. On the other hand, the State of Paraná has specific hiring methods for indigenous teachers, however, in the only indigenous school in the municipality, most of the hired teachers are not indigenous. This reality indicates the need to advance existing legislation at the municipal level so that the bilingual and differentiated pedagogical practice can be implemented in schools where there are indigenous students enrolled